epanggulan Creative Percussion “Labuhan Agni” | Tabuh Kreasi Pepanggulan “Labuhan Agni” - I Kadek Bayu Wedanta (GHURNITA: Jurnal Seni Karawitan, 2023)
Labuhan Agni Pepanggulan's Creative Tabuh composition was inspired by the Labuh Api temple in Ungasan village, South Kuta District, Badung Regency. The emotion of fire is defined as one that resides in the human body. Traditional patrons in previously developed works are defined by the growth of musical elements that are poured into the gamelan media, Gong Kebyar, in Labuhan Agni compositions. The Panca Sthiti Ngawi Sani creation technique was employed in Labuhan Agni' composition work, which covers the stages of inspiration (ngawirasa), investigation (ngawacak), conception (ngarencana), execution (ngawangun), and production (ngawangun) (ngebah). Labuhan Agni composition works are divided into three sections, each of which is divided into three parts. The composing task lasts 12 minutes in total. The fulfillment of Labuhan Agni's composition works is projected to promote the creativity of young artists in Bali, allowing them to create works based on phenomena that exist in the surrounding environment and have a value of beauty and privilege in compositional works.